Pelatihan Manajemen Stok dan Digitalisasi Pembayaran untuk Warung Kelontong - Dewi Anjani; Yogi Bachtiar; Puti Retno Ali; Desi Novianti (LKP KARYA PRIMA KURSUS, 2026)
Grocery stalls are a pillar of Indonesia's micro-economy, yet most are still managed traditionally, with suboptimal stock recording, cost of goods sold (HPP) calculation, and digital technology utilization, making them less competitive than modern retail. This community service activity aimed to improve the managerial and digital competence of grocery stall owners in RT 004/RW 009, Tugu Sub-district, Cimanggis District, Depok City. The implementation method consisted of a two-day workshop integrating Industrial Engineering approaches (layout, stock management, HPP) with Informatics Engineering (digital cashier applications and QRIS optimization), followed by one month of online mentoring. The partners consisted of 18 stall owners. Evaluation was conducted through pre-tests, post-tests, and satisfaction questionnaires. The results showed that 94.4% of partner stalls already had QRIS, but only 41.2% used it actively before the training. Participants' average knowledge score increased from 41.6 to 81.9, representing a 96.9% increase; 83.3% of participants used digital cashier applications after the training, and the number of stalls actively using QRIS increased from 7 to 16, with average daily QRIS transactions rising from 2.8 to 9.2. The average satisfaction score reached 4.5 out of 5. This activity effectively improved managerial literacy and optimized the use of digital technology already owned by the participants.